2018
DOI: 10.1186/s12889-018-6090-5
|View full text |Cite
|
Sign up to set email alerts
|

Condom use social norms and self-efficacy with different kinds of male partners among Chinese men who have sex with men: results from an online survey

Abstract: BackgroundSocial norms and self-efficacy play important roles in promoting consistent condom use among men who have sex with men (MSM). Few studies have investigated the association between social norms, self-efficacy and consistent condom use with different kinds of male partners among MSM. We conducted an online survey of MSM to evaluate this in China.MethodsA cross-sectional online survey was conducted in 2015. Participants completed a validated questionnaire covering socio-demographic information, consiste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
10
1
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 50 publications
6
10
1
1
Order By: Relevance
“…Condom use consistency with regular partners was quite low (n = 70, 32.7%). This finding is supported by previous studies showing that when regular sex partners are involved, young MSM are likely to have condomless anal sex in China 32–36 and developed countries, such as Sweden 37 and New Zealand. 38 Particularly, a study among college student MSM in Beijing reported that believing in unnecessary condom use with a regular sex partner is a significant predictor of UAI.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Condom use consistency with regular partners was quite low (n = 70, 32.7%). This finding is supported by previous studies showing that when regular sex partners are involved, young MSM are likely to have condomless anal sex in China 32–36 and developed countries, such as Sweden 37 and New Zealand. 38 Particularly, a study among college student MSM in Beijing reported that believing in unnecessary condom use with a regular sex partner is a significant predictor of UAI.…”
Section: Discussionsupporting
confidence: 85%
“…In the current study, the participants with high condom use self-efficacy were likely to report condom use consistency in the past six months, consistent with previous studies. 32 , 40 , 41 Furthermore, in different exceptional circumstances, especially if the sex partner becomes angry at the request for condom use and when the sex partner is intoxicated, the rates of having confidence in consistent condom use markedly decreased at 75.7% (n = 162) and 81.8% (n = 175), respectively. This finding shows that the willingness to use condoms might be affected if their partners became unconscious due to alcohol or illicit drug use in this sample.…”
Section: Discussionmentioning
confidence: 99%
“…We used an online method to recruit participants for this study and our sample is more likely to be educated, younger, and have Internet access [43,44]. However, online technologies have been rapidly growing in use for sex-partner seeking among MSM [45].…”
Section: Discussionmentioning
confidence: 99%
“…First, for perceived barriers, some MSM individuals might believe that condom usage would affect the trust of intimacy [ 20 ], same-sex identity [ 21 ], or lower sexual pleasure during UAI [ 22 ], as a result of which they would choose not to use condoms. Second, self-efficacy of condom use usually refers to the reward and proper use of condoms and to the communication with partners concerning condom use [ 23 , 24 ]. MSM with a high self-efficacy of condom use might have strong confidence and awareness to maintain condom use behaviors during anal sex, whether with regular partners or nonregular partners.…”
Section: Discussionmentioning
confidence: 99%